Destination Branding and Its Influence on Tourist’s Satisfaction and Loyalty - Roostika, Ratna (Jurnal Manajemen Teknologi, 2012)
Brand is known as a valuable asset as it enables to differentiate from competitors offerings as well as to generate positive perceptions in the consumers’ mind. In the tourism sector, as part of winning competition, it is suggested that destination should also be branded. Destination brand is believed to enable a location to attract investment, business, and tourist which is then improving the local economy. The objective of this study is to empirically examine the structural model to understand the relationship between destination branding and tourist behavior in the tourism sector. Destination branding is built based on three elements namely destination image, perceived quality, and destination awareness while tourist behavior is represented by tourist satisfaction and loyalty. By applying purposive sampling, 150 valid questionnaires were analysed using Partial Least Squares. Results indicate that there were positive influences between perceived quality and brand awareness to satisfaction whereas brand image had no significant influence on satisfaction. Further, satisfaction significantly influenced loyalty.  Key words: Destination branding, destination image, perceived quality, destination awareness, and tourists’ behavior.  Brand dikenal sebagai asset perusahaan yang memungkinkan untuk memberikan pembedaan terhadap pesaing sekaligus sebagai pembangun citra positif terhadap pelanggan. Dalam sektor pariwisata, untuk menghadapi persaingan, suatu tempat sebaiknya juga memiliki merek (brand). Merek ini diharapkan mampu memberi daya tarik investasi, bisnis, dan wisatawan yang akan memperbaiki kondisi ekonomi daerah tujuan wisata. Tujuan dari studi ini untuk secara empiris menganalisis model structural dari brand tujuan wisata dan perilaku wisatawan. Brand tujuan wisata dibangun dari tiga komponen: citra tujuan wisata, persepsi kualitas, dan kesadaran merek. Perilaku wisatawan diwakili oleh komponen kepuasan dan loyalitas. Dengan menerapkan sampel purposive, diperoleh sampel yang valid sebanyak 150 responden. Hasil analisis menggunakan Partial Least Squares menunjukkan bahwa hanya persepsi kualitas dan kesadaran merek menunjukkan pengaruh signifikan terhadap kepuasan, sedang citra tujuan wisata tidak berpengaruh. Selain itu, kepuasan terhadap daerah tujuan wisata juga secara signifikan mempengaruhi loyalitas. Kata kunci: Merek tujuan wisata, citra tujuan wisata, persepsi kualitas, kesadaran merek dan perilaku wisatawan.